PENGARUH PENGUNGKAPAN ESG TERHADAP KINERJA KEUANGAN PERUSAHAAN (STUDI EMPIRIS PADA PERUSAHAAN SEKTOR KEUANGAN YANG TERDAFTAR DI BEI PERIODE 2017-2019) - Era Vivianti Husada; Susi Handayani (Jurnal Bina Akuntansi, 2021)
This study aims to examine the effect of ESG disclosure on financial performance within firm. By using sample of 80 firms in finance sector, listed in Indonesia Stock Exchange for 2017-2019, sample selected using purposive sampling technique.Financial performance measured by Return on Asset, Tobin’s Q, and Sales Growth, the analysis method used is multiple regression analysis. The result showed that ESG disclosure only affect Return on Asset simultaneously, furtheranalysis showed that none of the economic performance variables affected by ESG disclosure partially, instead control variable produce mixed result that affect financial performance variable itself.